Optimal Demographic Factors of Passenger Satisfaction in Upcoming Airport Cities using The Design Of Experiments - Nalla Ramakrishna, Dr. Harish Babu S (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Conventionally, the concept of design has a prominent role in engineering applications. It brings innovations in organizations and industries through its process. Also, most of the design processes are frequently verified statistically and experimentally. Over the years, Design of Experiments (DoE) has gained significant application in diverse industries and research firms as a mathematical method and also as a multipurpose applied statistical feature/tool. It is used in numerous ways like process design, process development, design input comparisons, and process optimization. Hence, DoE is a powerful instrument for any organization for the growth and expansion of its business. And one of the means of a firm's growth (public or private) is customer satisfaction. Simply said, customer satisfaction refers to the identification and fulfillment of customer's requirements or needs as per their specifications. In this regard, this study aims to explore a unique application of DoE concerning passenger satisfaction of their travel to the nearest airport city. First, adding air transportation mode to any tier 2 and tier 3 cities in India requires an important decision concerning the passenger satisfaction of existing travel modes/types. In other words, it refers to generating an optimum combination of those who travel to the nearest airport city, i.e., passenger demographics whose responses serve as inputs for the study. The responses were collected on multiple factors concerning the satisfaction scale. On analysis, these factors & optimal inputs for responses revealed interesting insights into the plan and design of services accordingly. In this regard, the paper aims to get the optimal combination of responses by constructing a factorial design and also conduct a response optimization experiment for a factorial design..